The Traumatic Experience of Breast Cancer: Which Factors Can Relate to the Post-traumatic Outcomes? - Romeo, Annunziata; Di Tella, Marialaura; Ghiggia, Ada; Tesio, Valentina; Gasparetto, Eleonora; Stanizzo, Maria Rosa; Torta, Riccardo; Castelli, Lorys (Frontiers in Psychology, 2019)
Background: Post-traumatic growth (PTG) is considered a positive outcome of struggling with a traumatic event, distinct and opposite from negative outcomes, i.e. psychological distress. The present study aimed to shed light on the relationship between potentially relating factors (i.e. coping strategies, perceived social support, and attachment style) and both positive and negative psychological outcomes. Methods: A total of 123 breast cancer survivors were recruited, who completed a battery of self-report questionnaires, assessing PTG, psychological distress, coping strategies, perceived social support, and attachment style. Three regression analyses were run to evaluate whether relating factors were significant predictors of the positive and negative psychological outcomes. Results: The regression analyses showed that the ‘Fatalism’ coping strategy and perceived social support were two significant predictors of PTG. Instead, the ‘Helpless-Hopeless’ and ‘Anxious Preoccupation’ coping strategies, as well as an insecure attachment style, were significant predictors of depression, while the ‘Anxious Preoccupation’ coping strategy and an insecure attachment style were significant predictors of anxiety. Conclusions: The present findings showed that the factors underlying a positive or negative outcome are different and specific. While perceived social support and a fatalistic attitude seem to play a key role in the positive outcome, dysfunctional coping strategies, together with an insecure attachment style, appear to be related with negative psychological outcome. Considering these factors in clinical practice would help patients to give meaning to their traumatic experience, enhancing psychological growth.